1998
DOI: 10.1002/hep.510280308
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial hemodynamic effects of bosentan, a mixed ETA and ETB receptor antagonist, in portal hypertensive rats

Abstract: In patients with cirrhosis, the plasma level of endothelin, a potent vasoconstrictor peptide, is elevated, and endothelin plays a role in increased intrahepatic vascular resistance. Thus, the aim of this study was to evaluate the hemodynamic effects of bosentan, a mixed ET A and ET B endothelin receptor antagonist in three models of portal hypertension. In all groups of rats, endothelin (2 g/kg intravenously) administration significantly increased intrahepatic vascular resistance. In rats with secondary biliar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
52
1
7

Year Published

1999
1999
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(61 citation statements)
references
References 32 publications
1
52
1
7
Order By: Relevance
“…[4][5][6]15,23,24 However, the vasoactivity of ET-1 on the collateral circulation has never been done before. This study shows that ET-1 has a direct vasoconstrictive effect on the collateral vessels of portal hypertensive rats and may consequently increase the collateral vascular resistance and participate in the development and maintenance of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6]15,23,24 However, the vasoactivity of ET-1 on the collateral circulation has never been done before. This study shows that ET-1 has a direct vasoconstrictive effect on the collateral vessels of portal hypertensive rats and may consequently increase the collateral vascular resistance and participate in the development and maintenance of portal hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…5 Recently, it has been shown that bosentan, a nonselective endothelin receptor antagonist, significantly reduced the portal pressure of portal hypertensive rats. 15 However, it is not clear if ET-1 could modulate portal pressure by a direct constrictive effect on the collateral vessels of portal hypertensive rats.The aims of this study were to investigate the vascular activity and the receptor-mediated effects of ET-1 on the portalsystemic collaterals of portal hypertensive rats. The regulation of nitric oxide (NO) and prostaglandin on the effects of ET-1 was also evaluated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12-13 Endothelin receptors expression is increased in portal hypertensive rats 14 and bosentan, a mixed ET A and ET B receptor antagonist, lowers portal pressure in cirrhotic rats, as well as portal vein stenosed animals. 15 Thus, indirect evidence suggests that ET-1 can act as a paracrine or autocrine factor contributing to increased resistance to portal flow in the liver.Endothelins act on 2 types of receptors, the A receptor, the B receptor, 16 and probably a C receptor; ET-1 has a greater affinity for A receptors, which mediate vasoconstriction. Endothelin B receptors expressed on endothelial cells mediate transient vasodilatation, probably through the stimulation of NO and prostaglandin I 2 (PGI 2 ) production; B receptors on smooth muscle may also mediate vasoconstriction.…”
mentioning
confidence: 99%
“…[12][13] Endothelin receptors expression is increased in portal hypertensive rats 14 and bosentan, a mixed ET A and ET B receptor antagonist, lowers portal pressure in cirrhotic rats, as well as portal vein stenosed animals. 15 Thus, indirect evidence suggests that ET-1 can act as a paracrine or autocrine factor contributing to increased resistance to portal flow in the liver.…”
mentioning
confidence: 99%